Investigation of flood monitoring & detection system using iot application - Muhammad Syafiq, Zainal (2022)
This research was conducted to investigate the performance of the Flood Monitoring & Detection System applying Internet of Thing (IoT) with solar system as a backup source. A flood is a catastrophe that happens unexpectedly and unpredictably. It is a disaster that often happens every year, especially once during the monsoon season. With the development of technology nowadays, it can help people’s that live in the flood risk areas daily lives become easier. Flood Monitoring and Detection technology with warning system is built to monitor and warn people living in areas a high risk for floods so that they are always prepared for floods before it happens. This project is applying the Internet of Thing (IoT) which is applying the wireless connection concept. The system is completely controlled by one of the great Microcontroller technologies, namely the ESP8266 NodeMcu, this microcontroller system can be designed according to a set program. This system requires some programming part for interfacing. Ultrasonic sensor is used in this to transfer the signal into the microcontroller board for the data output signal analysis. In current world, internet is the very most important thing nowadays, it also can be applied anytime and everywhere. Users can monitor the current situation of river water level on the application. In addition, this device also constructs as a back-up energy source with the presence of solar energy, which can be longer lasting and effective compared to conventional flood detection systems.